(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1977)
A case o f double esophageal diverticulum in a female Pinscher 4 years old isdescribed. Radiographic examination associated to necrological aspects and clinic symptoms are presented.